Implementing strength training strategies for injury prevention in soccer: Scientific rationale and methodological recommendations - Beato, M.; Maroto-Izquierdo, S.; Turner, A. N.; Bishop, C. (International Journal of Sports Physiology and Performance, 2021)
Due to the negative effects that injuries have on performance, club finances, and long-term player health (permanent disability after a severe injury), prevention strategies are an essential part of both sports medicine and performance. Purpose: To summarize the current evidence regarding strength training for injury prevention in soccer and to inform its evidence-based implementation in research and applied settings. Conclusions: The contemporary literature suggests that strength training, proposed as traditional resistance, eccentric, and flywheel training, may be a valid method to reduce injury risk in soccer players. Training strategies involving multiple components (eg, a combination of strength, balance, plyometrics) that include strength exercises are effective at reducing noncontact injuries in female soccer players. In addition, the body of research currently published supports the use of eccentric training in sports, which offers unique physiological responses compared with other resistance exercise modalities. It seems that the Nordic hamstring exercise, in particular, is a viable option for the reduction of hamstring injuries in soccer players. Moreover, flywheel training has specific training peculiarities and advantages that are related to the combination of both concentric and eccentric contraction, which may play an important role in injury prevention. It is the authors` opinion that strength and conditioning coaches should integrate the strength training methods proposed here in their weekly training routine to reduce the likelihood of injuries in their players; however, further research is needed to verify the advantages and disadvantages of these training methods to injury prevention using specific cohorts of soccer players.